A cross layer approach for efficient thermal management in 3D stacked SoCs. (June 2016) - Jung, Matthias; Weis, Christian; Wehn, Norbert
Abstract: 3D stacking of silicon dies via Through Silicon Vias (TSVs) is an emerging technology to increase performance, energy efficiency and integration density of today's and future System-on-Chips (SoCs). Especially the stacking of Wide I/O DRAMs on top of a logic die is a very promising approach to tackle the memory wall and energy efficiency challenge. The potential of this type of stacking is currently under investigation by many research groups and companies in particular for mobile devices. There, for instance, the baseband processing and the application processor can be implemented on the same single logic die. On top of this die one or several Wide I/O DRAMs are stacked. An example of such a SoC is the WIOMING chip [15]. However, new challenges emerge, especially thermal management, which is already a very demanding challenge in current 2D SoCs. With 3D SoCs this problem exacerbates due to reliability issues such as the temperature sensitivity of DRAMs, i.e., the retention time of a DRAM cell largely decreases with increasing temperature. In this paper, we show a holistic cross layer reliability approach for efficient reliability management starting from measuring and modeling of DRAM retention errors, which finally leads to optimizations for specific applications. These optimizations exploit the data lifetime and the inherent error resilience of the application, which is for instance given in the probabilistic behavior of wireless communications. Highlights: We measure the retention times and provoked bit errors of WIDE I/O DRAM dies on top of a SoC logic die. We propose a calibrated DRAM retention error model based on measurements, which can be integrated into system simulators. With this model we show that dedicated applications can tolerate DRAM retention errors.